DAMPAK KRISIS FINANSIAL GLOBAL TERHADAP PHK - Sriningsih, Endang (Program Doktor Ilmu Ekonomi, 2009)
Crisis financial happened in latter months truly begin inUnited States. But the impact or effect to other nations, includingIndonesia, cannot be obviated. Many circle of predicting this crisis inIndonesiawill start felt in the year next. Possibly continue until year 2010. The decline of material requisition inAmericanStateand Japan for State of purpose ofIndonesiaexporting result the light sectors this exporting and result threat disconnection of job everywhere. So also some the companies inSurabaya, there is about 11 company, they have raised PHK to the employees, is mostly is medium scale company.Â Crisis knocking over in this time still early. Estimate, crisis culminate at mid of knowing 2009. In this time sector is real will feel guncangan very heavy. For anticipating kemungkinahn crisis obsolesce financial the is global have to be looked by the solution, is more than anything else cure of economics inIndonesianot so strong. This thing is seen fromIndonesiaforeign exchange reserve which still weakens. At least, butuh time of two until three year for returning was normal. To break this financial crisis impact of government require to do inter alia: (1) Government have to pay attention to UMKM, (2) Program Nasional Pemberdayaan Masyarakat (PNPM), (3) Reinforcement Of Performance Exported, and (4) Strengthen Economics Base on independence.Â Keyword: Global crisis impact and PHK